Inhibition of glucosylceramide synthase stimulates autophagy flux in neurons. (3rd March 2014) - Shen, Wei; Henry, Anastasia G.; Paumier, Katrina L.; Li, Li; Mou, Kewa; Dunlop, John; Berger, Zdenek; Hirst, Warren D.
Abstract Aggregate‐prone mutant proteins, such as α‐synuclein and huntingtin, play a prominent role in the pathogenesis of various neurodegenerative disorders; thus, it has been hypothesized that reducing the aggregate‐prone proteins may be a beneficial therapeutic strategy for these neurodegenerative disorders. Here, we identified two previously described glucosylceramide (GlcCer) synthase inhibitors, DL‐threo‐1‐Phenyl‐2‐palmitoylamino‐3‐morpholino‐1‐propanol and Genz‐123346(Genz), as enhancers of autophagy flux. We also demonstrate that GlcCer synthase inhibitors exert their effects on autophagy by inhibiting AKT‐mammalian target of rapamycin (mTOR) signaling. More importantly, siRNA knock down of GlcCer synthase had the similar effect as pharmacological inhibition, confirming the on‐target effect. In addition, we discovered that inhibition of GlcCer synthase increased the number and size of lysosomal/late endosomal structures. Although inhibition of GlcCer synthase decreases levels of mutant α‐synuclein in neurons, it does so, according to our data, through autophagy‐independent mechanisms. Our findings demonstrate a direct link between glycosphingolipid biosynthesis and autophagy in primary neurons, which may represent a novel pathway with potential therapeutic value for the treatment of Parkinson's disease. <boxed-text content-type="graphic" id="jnc12672-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text> Inhibition of GlcCer synthase enhances autophagy by inhibiting AKT‐mTOR signaling, and increases the number and size of lysosomal/late endosomal structures. Furthermore, inhibition of GlcCer synthase decreased levels of mutant α‐synuclein in neurons, which may represent a potential therapeutic target for Parkinson's disease.